Úton a rendszerváltoztatás felé : A gazdasági kamarák narratívái az államszocializmus utolsó éveiben - Zachar, Péter Krisztián (Közép-Európai Közlemények, 2017)
The present study examines the situation and change of chambers of economy in Hungary during the period of state-socialism. The chambers of industry and commerce have a long history in Hungary: the first chambers were established during the 19th century and proved to be indispensable in the fields of economy. The chambers increased the intensity of their own initiatives during the period between the two world wars: they played an important role in organising the Budapest International Fair, in supporting the commercial school network or (in partnership with the state) in the economic integration of the territories regained after 1938. After 1945, however, these organisations were not able to further improve their activities, what is more, most of them were eliminated by the totalitarian communist rule. From the end of the Second World War to the 1989/1990 regime change, only one organisation was operating in the field of economy which called itself chamber: The Chamber of Commerce, however, was a mere shadow of its predecessor. It did not have any regional bodies, it was not allowed to perform interest representation work, it was only permitted to carry out certain tasks in connection with foreign trade under supervision of delegates from the communist party. Following the economic, then political changes starting in the middle of the 1980s resulting from the oil crisis and Hungary’s accession to the International Monetary Fund, the players of commerce and industry also demanded with increasing emphasis an organisation to represent their interests. Thus the operation of the chamber was expanded, and the organisation – later called Hungarian Economic Chamber –had regional committees as well. The present study gives a deeper insight into the evolving processes of chamber-transformation and the role of the chamber of economy in the regime change.